Intumescent geopolymer-bound coatings for fire protection of steel - Watolla, M.; Gluth, G.; Sturm, P.; Rickard, William; Krüger, S.; Schartel, B. (2017)
© 2017 Göller Verlag. The passive fire protection of steel structures and other load-bearing components will continue to gain importance in future years. In the present contribution, novel intumescent aluminosilicate (geopolymer-bound) composites are proposed as fire-protective coatings on steel. Steel plates coated with these materials were exposed to the standard temperature-time curve as defined in ISO 834-1:1999. The coatings partially foamed during curing and expanded further during thermal exposure, demonstrating their intumescent characteristic.Thermogravimetryandoscillatory rheometry determined that the intumescent behavior is attributed to a transition to a viscous state (loss factor > 1) in the temperature range of major water release, differing from conventional geopolymers. XRD and SEM images showed that the coatings had characteristics of ceramic or glass-ceramic foams after fire resistance testing, suggesting superior performance under challenging conditions. The thickness of the coatings influenced their foaming and intumescent behavior and thus the time for the coated steel plates to reach 500 °C. A number of additives were also studied with the best performance obtained from samples containing sodium tetraborate.Acoating of just 6mmwas able to delay the time it takes for a steel substrate to reach 500 °C t o more than 30 minutes.